2010
DOI: 10.1016/s0049-3848(10)70017-7
|View full text |Cite
|
Sign up to set email alerts
|

Antimetastatic activities of heparins and modified heparins. Experimental evidence

Abstract: Heparin is commonly used for prevention or treatment of cancer-associated thromboembolism. Recent clinical evidence indicates that heparin, and low-molecular weight heparin improves survival of cancer patients. Experimental evidence from various animal models consistently supports the ability of heparin to attenuate metastasis. Heparin, apart from its anticoagulant activity contains a variety of biological activities possibly affecting cancer progression, including: inhibition of heparanase, blocking of P-and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 66 publications
1
83
0
1
Order By: Relevance
“…A recent report indicated an additional chemo-sensitizing activity of heparin through inhibition of P-glycoprotein-mediated multidrug resistance [31]. The results of "in vitro", "in vivo" studies and clinical trials have been reviewed [29,[32][33][34]. Retrospective evaluation of early clinical trials indicated that heparin can provide survival benefits to cancer patients compared to other anti-thrombotics [32].…”
Section: Anticancer Activity Of Heparin and Lmwhsmentioning
confidence: 99%
“…A recent report indicated an additional chemo-sensitizing activity of heparin through inhibition of P-glycoprotein-mediated multidrug resistance [31]. The results of "in vitro", "in vivo" studies and clinical trials have been reviewed [29,[32][33][34]. Retrospective evaluation of early clinical trials indicated that heparin can provide survival benefits to cancer patients compared to other anti-thrombotics [32].…”
Section: Anticancer Activity Of Heparin and Lmwhsmentioning
confidence: 99%
“…heparanase) and formation of the capillary vessel lumen (Marchetti et al, 2008). Moreover, tissue factor (TF) and its natural inhibitor (TFPI) are also important heparin-binding proteins that perform well-recognized roles in the regulation of angiogenesis, tumor growth and metastasis (Bobek & Kobarik, 2004;Borsig, 2010;Debergh et al, 2010;Norrby, 2006). LMWH may influence angiogenesis through modulation of the expression of angiogenic growth factors (VEGF and bFGF) and their inhibitors (Dogan et al, 2011;Gasowska et al, 2009;Mousa & Petersen, 2009).…”
Section: Bemiparin Badyketmentioning
confidence: 99%
“…Several molecular mechanisms exist to explain the antimetastatic efficiency of heparin. The reader is referred to excellent reviews in this field (Borsig, 2010;Casu et al 2008) from which the inhibitory capacity of heparin towards P-and L-selectin binding should be highlighted here. Heparin as a highly sulfated, acidic polysaccharide has the ability to compete with the natural mucin-like selectin ligands.…”
Section: The Role Of Heparin For Antimetastatic Approachesmentioning
confidence: 99%